Examining self-reported aberrant behavior among Lebanese drivers using the Driver Behavior Questionnaire (DBQ) - Dalal Youssef; Pascale Salameh; Linda Abou-Abbas; Louis-Rachid Salmi (Springer, 2023)
Abstract Background The Driver Behavior Questionnaire (DBQ) is one of the most used tools for measuring self-reported aberrant driving behavior. Several versions of the DBQ exist varying in terms of the item number and factor structure. Objectives This study aimed to investigate the psychometric properties and the factorial structure of the DBQ for assessing aberrant behavior among Lebanese drivers and to examine the relationship between DBQ subscales and socio-demographic characteristics and traffic-related variables. Methods A cross-sectional study was conducted among Lebanese drivers aged over 18 years from all Lebanese governorates. Data were collected using a convenient sampling technique and an anonymous Arabic self-administered questionnaire that included socio-demographic characteristics and the Arabic Lebanese version of the DBQ (DBQ-L). Statistical analyses were performed using SPSS version 24 and Amos software. Exploratory factor analysis (N = 568) and confirmatory factor analysis (N = 534) were used to test the factorial structure of the DBQ-L. Linear regression analyses were performed to examine the association between DBQ-L, sociodemographic, and relevant traffic variables. Results A total of 1102 drivers aged between 18 and 82 years participated in the study with an average age of 34.64 (SD = 12.33). Of the total, 68.4% of participants were male with an average driving experience of 13.46 years (SD = 10.76). The DBQ-L total scale revealed high internal consistency (Cronbach's α = 0.892). Exploratory and confirmatory factor analysis supported the original four-factor structure reflecting aggressive violations, ordinary violations, errors, and lapses dimensions. Aggressive violations had the highest mean among all the DBQ subscales. Men were found to have a higher tendency to commit aggressive and ordinary violations than females. Furthermore, the ordinary violation score was positively associated with younger age and increased mileage. All DBQ subscales decreased with the highest educational level. Being a professional driver increased the likelihood of drivers reporting violations, errors, and lapses, and increased mileage amplified the tendency of displaying aggressive violations and lapses when driving. However, errors decreased for young drivers and increased with age and larger driver experience. Conclusion The cross-cultural adapted version of the DBQ was found to be a reliable and valid tool for assessing aberrant behaviors among Lebanese drivers. This study revealed distinct behavior patterns, with men frequently displaying aggressive violations, and younger, high-mileage drivers more prone to ordinary violations and lapses. Higher education correlated with safer driving, while professional drivers reported more violations, errors, and lapses. These findings highlight the importance of tailored road safety interventions based on driver demographics. Further studies are needed to examine the ability of DBQ to predict road accidents.